Improving Live Sequence Chart to Automata Transformation for Verification - Kumar, Rahul; Mercer, Eric (Electronic Communications of the EASST, 2008)
This paper presents a Live Sequence Chart (LSC) to automata transformation algorithm that enables the verification of communication protocol implementations. Using this LSC to automata transformation a communication protocol implementation can be verified using a single verification run as opposed to previous techniques that rely on a three stage verification approach. The novelty and simplicity of the transformation algorithm lies in its placement of accept states in the automata generated from the LSC. We present in detail an example of the transformation as well as the transformation algorithm. Further, we present a detailed analysis and an empirical study comparing the verification strategy to earlier work to show the benefits of the improved transformation algorithm.